Photovoice as a platform for empowerment of women with disability - Diane Macdonald; Karen Peacock; Angela Dew; Karen R. Fisher; Katherine M. Boydell (Elsevier, 2022)
Photovoice is documented as an inclusive and empowering research method that amplifies the voice of marginalised groups. However, in feminist photovoice projects with women, many studies make claims about empowerment, but the claims are seldom evaluated or evidenced. Our photovoice research focused on identity and inclusion of women with physical disability. In this paper, we pose the question: how do the women describe or illustrate personal meanings and examples of empowerment that occurred through the project? Photographs, words, discussions and interviews were thematically analysed through Kieffer's three dimensions of empowerment framework. We determined that photovoice provides a process and a platform to increase self-awareness, consciousness of shared experiences and agency to act. Photovoice creates a space for photographers to exercise power, shape images and convey ideas about their lived experiences. Their photographs, words and actions add knowledge that can inform and influence social change in the community, including disability practice, research and health promotion.